2012
DOI: 10.1111/j.1365-4632.2012.05541.x
|View full text |Cite
|
Sign up to set email alerts
|

Human leukocyte antigens class I and class II in patients with pemphigus in southern Turkey

Abstract: The results suggest that DRB1*04, DRB1*14, DQB1*05, and DPB1*0401 class II HLAs and A*11 and CW*01 class I HLAs are associated with pemphigus in southern Turkey. Observed differences in LD patterns between patients and controls suggest that the coexistence of the respective alleles is strongly determinant of predisposition towards (DRB1*14/DQB1*05 and A*11/DQB1*05) or protection against (B*50/DQB1*02) the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 24 publications
3
18
0
4
Order By: Relevance
“…Interestingly, the DPB1*04:01 allele has been associated with other autoimmune diseases showing both a protective effect for type 1 diabetes (21) and for multiple sclerosis ( 22 ), as well as an increased risk for rheumatoid arthritis (23), pemphigus (24), and vasculitis (25). To our knowledge, the association between DPB1*04:01 and CDA or CD has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the DPB1*04:01 allele has been associated with other autoimmune diseases showing both a protective effect for type 1 diabetes (21) and for multiple sclerosis ( 22 ), as well as an increased risk for rheumatoid arthritis (23), pemphigus (24), and vasculitis (25). To our knowledge, the association between DPB1*04:01 and CDA or CD has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies, often utilizing serum, have addressed the HLA haplotype distribution utilizing ABD cases and controls [5,6,[12][13][14][15]. These studies concluded that some HLA alleles strongly predispose toward and/or protect against ABDs.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Pemphigus vulgaris (PV) mainly produces autoantibodies against desmoglein 3, while pemphigus foliaceus (PF) mainly produces autoantibodies against desmoglein 1. [6][7][8][9] The disease usually manifests between the fourth and sixth decade. If untreated, widespread erosion and blisters may occur with major consequences, even death.…”
Section: Introductionmentioning
confidence: 99%